Prerequisites for the Implementation of a Risk-Oriented MRO Strategy for NPP Valves - A. A. Lapkis; V. N. Nikiforov; P. V. Povorov; M. V. Kalashnikov; E. S. Arsentieva (Глобальная ядерная безопасность, 2022)
The paper considers the relevance and possibility of developing methodological foundations for risk-oriented strategy of nuclear power plant equipment MRO on the example of pipeline valves. The pre-design study of the information system implementing these fundamentals is described.